Deep work ebook Rules for focused success in a distracted world. - Newport, Cal (2016)
From a New York Times bestselling author, learn to master one of our economy’s rarest skills–the ability to focus–and achieve groundbreaking results. Deep work is the power to focus without distraction on a cognitively demanding task. It allows you to quickly master complicated information and produce better results in less time–a superpower in our increasingly competitive economy. In Deep Work , author and professor Cal Newport presents four rules for transforming your mind and habits to support this skill: 1. Work Deeply  2. Embrace Boredom  3. Quit Social Media  4. Drain the Shallows  A mix of cultural criticism and actionable advice, Deep Work uses examples from Carl Jung to social media pioneers to demonstrate how great thinkers have focused their minds in a nonstop world.